THE STUDY OF THE HISTORICAL GEOGRAPHY OF NAKHCHIVAN IN THE 19TH-20TH CENTURIES IN THE PERİOD OF INDEPENDENCE IN AZERBAIJANI HISTORIOGRAPHY - Aliyeva, Nurlana (International Journal of Innovative Technologies in Social Science, 2023)
The main goal of writing the article is to systematically analyze the research conducted in the historiography of Azerbaijan during the period of independence, related to the historical geography of Nakhchivan in the 19th and 20th centuries. One of the main issues is related to the points highlighted by the authors from Azerbaijan in the researches related to the historical geography of Nakhchivan. During the writing of the article, both general research methods and methods of a special nature for historical science were used. However, the main methods were systematic analysis and content analysis. A systematic analysis of numerous research works written in this direction was carried out and they were grouped. Later, content analysis and comparative analysis of the works were carried out separately. The conclusion is that the claims made against the territories of the country such as Karabakh and Nakhchivan were one of the main factors determining the relevance of these studies.